A Fluorescence and Molecular Docking Study on the Interaction of 4′-Hydroxychalcone with Bovine Serum Albumin and Human Serum Albumin - Patar, Madhumita; Jalan, Ankita; Shaemningwar Moyon, N. (Asian Journal of Chemistry, 2022)
The interaction of 4′-hydroxychalcone (4′HC) with bovine serum albumin (BSA) and human serum albumin (HSA) was studied under physiological condition (pH=7.0). The fluorescence intensity of both serum albumins was quenched in presence of 4′HC at different temperatures. Stern-Volmer analysis and bimolecular quenching constants indicates the presence of static quenching in BSA. Whereas, fluorescence quenching of HSA is due to both the mechanism of static and dynamic quenching. The formation of ground state complex is further confirmed by absorption spectroscopy. The interaction of 4′HC with BSA is stronger than with HSA. FRET study shows the possible energy transfer between 4′HC with BSA and HSA. The binding site of the protein was identified by molecular docking study. The FTIR and CD analysis indicates conformational change in both the serum albumins. The thermodynamic study indicates that the association of BSA and HSA with 4′HC is spontaneous, enthalpy driver and involves electrostatic force of interaction.